Lack of energetic equivalence in forest soil invertebrates. Issue 2 (1st February 2014) - Ehnes, Roswitha B.; Pollierer, Melanie M.; Erdmann, Georgia; Klarner, Bernhard; Eitzinger, Bernhard; Digel, Christoph; Ott, David; Maraun, Mark; Scheu, Stefan; Brose, Ulrich
Abstract : Ecological communities consist of small abundant and large non‐abundant species. The energetic equivalence rule is an often‐observed pattern that could be explained by equal energy usage among abundant small organisms and non‐abundant large organisms. To generate this pattern, metabolism (as an indicator of individual energy use) and abundance have to scale inversely with body mass, and cancel each other out. In contrast, the pattern referred to as biomass equivalence states that the biomass of all species in an area should be constant across the body‐mass range. In this study, we investigated forest soil communities with respect to metabolism, abundance, population energy use, and biomass. We focused on four land‐use types in three different landscape blocks (Biodiversity Exploratories). The soil samples contained 870 species across 12 phylogenetic groups. Our results indicated positive sublinear metabolic scaling and negative sublinear abundance scaling with species body mass. The relationships varied mainly due to differences among phylogenetic groups or feeding types, and only marginally due to land‐use type. However, these scaling relationships were not exactly inverse to each other, resulting in increasing population energy use and biomass with increasing body mass for most combinations of phylogenetic group or feeding type with land‐use type. Thus, our results are mostly inconsistent with the classic perception of energetic equivalence, and reject the biomass equivalence hypothesis while documenting a specific and nonrandom pattern of how abundance, energy use, and biomass are distributed across size classes. However, these patterns are consistent with two alternative predictions: the resource‐thinning hypothesis, which states that abundance decreases with trophic level, and the allometric degree hypothesis, which states that population energy use should increase with population average body mass, due to correlations with the number of links of consumers and resources. Overall, our results suggest that a synthesis of food web structures with metabolic theory may be most promising for predicting natural patterns of abundance, biomass, and energy use.